2004
DOI: 10.1146/annurev.publhealth.25.101802.123042
|View full text |Cite
|
Sign up to set email alerts
|

International Differences in Drug Prices

Abstract: Key Words prescription drugs, price discrimination, pharmaceutical research and development, drug price regulation s Abstract This paper addresses how and why drug prices differ across countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 15 publications
(23 reference statements)
1
35
0
Order By: Relevance
“…Schut and van Bergeijk (1986) test the existence of international price discrimination in the pharmaceutical industry using trade data for 32 countries and conclude that drug prices are highly influenced by purchasing power of a country. Wagner and McCarthy (2004) come to a similar conclusion, finding that price differences exist across countries; however, the differences are rather small. Lichtenberg (2011) finds evidence that pharmaceutical companies charge lower prices in low-income countries than in developed countries.…”
Section: Related Literaturementioning
confidence: 61%
“…Schut and van Bergeijk (1986) test the existence of international price discrimination in the pharmaceutical industry using trade data for 32 countries and conclude that drug prices are highly influenced by purchasing power of a country. Wagner and McCarthy (2004) come to a similar conclusion, finding that price differences exist across countries; however, the differences are rather small. Lichtenberg (2011) finds evidence that pharmaceutical companies charge lower prices in low-income countries than in developed countries.…”
Section: Related Literaturementioning
confidence: 61%
“…1 Studies have documented much pharmaceutical price variation across countries; one study found that wholesale costs tend to be higher in the United States than abroad. 2 A recent comparison of U.S. wholesale drug prices with those in eight other nations found that for the 249 most frequently used agents, only Japan had higher prices than the United States had, with prices in the other countries averaging 6-33 percent lower. 3 Consequently, policymakers have proposed measures to bring U.S. prices in line with international norms.…”
mentioning
confidence: 99%
“…Energy and fuel taxes are ubiquitous among Nordic countries, and though the level of taxes on gasoline and diesel automotive fuel varied in each of the Nordic economies, automotive fuel taxes (both for gasoline and diesel) in the Nordics are among the highest in the world (Figure 1.26) (Parry et al, 2014;Wagner, 2014). Diesel tended to be taxed at lower rates (in both in terms of carbon emissions and in absolute terms) than gasoline.…”
Section: Current Policies and Goalsmentioning
confidence: 99%
“…Denmark, Sweden and Norway have ambitions of complete carbon neutrality (including transport) by 2050, while Finland targets an 80% GHG reduction and Iceland a 50%-70% reduction in GHG levels (both relative to 1990 levels). Even more ambitious goals have been set for Nordic cities: for instance, Copenhagen has set a goal to achieve carbon neutrality by 2025, and Oslo aims to reduce its GHG emissions by 95% relative to 1990 levels by 2030.Energy and fuel taxes are ubiquitous among Nordic countries, and though the level of taxes on gasoline and diesel automotive fuel varied in each of the Nordic economies, automotive fuel taxes (both for gasoline and diesel) in the Nordics are among the highest in the world (Figure 1.26) (Parry et al, 2014;Wagner, 2014). Diesel tended to be taxed at lower rates (in both in terms of carbon emissions and in absolute terms) than gasoline.…”
mentioning
confidence: 99%